A Semianalytical Model for Analyzing the Infill Well-Caused Fracture Interference from Shale Gas Reservoirs. (1st November 2021) - Fang, Sidong; Wu, Yonghui; Dai, Cheng; Ma, Liqiang; Liu, Hua
Abstract : Drilling infill well has been widely used in many plays to enhance the recovery of shale gas, but the infill well-caused fracture interference is a very important issue that should be taken into consideration. The well interference makes it difficult for the conventional models to make production predictions, fracture characterization, and production data analysis. In this paper, a semianalytical model is proposed for this purpose by discretizing the whole control volume of the parent and infill wells into several linear flow zones. In this way, three important issues can be further handled very naturally, including fracture connection between the parent and infill wells, different SRV properties for zones with different distances to the wellbore, and different production times for adjacent wellbores. The approximate expressions for different flow regimes are used in making production predictions in the time domain, and a flowing material balance method and a simple iteration are used to update the model parameters step by step. The proposed model is shown to be reasonable and accurate for handling multiwell interference problems after comparing with the commercial numerical simulator tNavigator. The synthetical cases show that the fracture parameters, SRV properties, and well infill time have a significant influence on the production performance of both the parent and infill wells. The results show that the production of the parent well will be dramatically enhanced when it is connected with the infill well via high-conductive hydraulic fractures. Longer unconnected fractures and more fracturing stages/clusters for the infill well will result in higher production for the infill well, but a negative effect is observed for the parent well. The permeability of the distant well SRV has a similar influence on the parent and infill wells. The results also show that late time well interference will result in a more significant increase in production rate on the log-log plots for the severe depletion around the parent well. Finally, the proposed model is used to analyze the production data of a field case from Fuling shale in Southwestern China. After analyzing the production data, several parameters can be obtained for both parent and infill wells, including the fracture lengths and conductivities, numbers of connected fractures, and the near and distant well permeabilities of the SRV. This gives a basic and practical technique for production prediction, formation and fracture evaluation, and well connectivity analysis from shale gas wells with fracture connection.